Safety assessment of monosodium glutamate based on intestinal function and flora in mice - Jinzhao Xu; Mengqi Tang; Yini Liu; Jinghan Xu; Xiaoxi Xu (Food Science and Human Wellness)
Although monosodium glutamate (MSG) is a widely used food additive, its safety and systemic side effects have not been fully clarified. The intestinal flora is closely associated with human health; however, it remains unclear whether MSG consumption can affect health by acting on the intestinal flora. In this study, serum biomarkers, intestinal structure, intestinal immunity, and intestinal flora were examined to investigate the effects of different doses of sodium glutamate on the body, intestinal function, and intestinal flora of mice. The results showed that 30 mg/kg MSG had no significant effect on serum C-reactive protein, trimethylamine N-oxide, angiotensin II, intestinal interleukin (IL)-1β, IL-6, tumor necrosis factor-α, secretory IgA and fecal albumin in mice, but also promoted intestinal development and regulated the intestinal flora. Moreover, 1500 mg/kg MSG increased the risk of cardiovascular disease and damaged the intestinal structure and flora. In this study, MSG was also found to be healthier than salt at the equivalent sodium concentration. Collectively, these findings suggested that low doses of MSG were safe for mice and may have some health benefits as a probiotic by promoting intestinal development and regulating the intestinal flora.